Maintaining focus, energy, and options over the career - Baugh, S. Gayle; Sullivan, Sherry E., 1961- (Research in careers., 2009)
The first volume of the series, Maintaining Focus, Energy, and Options Over the Career, examines how individuals enact and keep their career vital over their work life. Awarding-winning, internationally renowned researchers, including Daniel Feldman, Jennifer Deal, Phyllis Tharenou, and Terry Beehr examine the dynamic nature of contemporary careers and how careers change as individuals change in response to such factors as aging, learning, experience or contextual changes. Volume 1 includes theoretical perspectives on maintaining person-environment "fit" over the course of the career, the shifting constellation of developmental relationships over time and place, a new framework for examining midcareer renewal, a reconceptualization of the retirement transition, and potential gender differences in self-initiated international careers. Empirical studies in volume 1 examine provocative questions including: Is the traditional career really dead? Are there significant generational differences in learning and development? Can career plateauing be positive for the individual or the organization? The focus throughout this volume is on how careers unfold over time and how individuals remain productive and successful as they navigate career changes.